DECK OF LIVES - Euodia Y Pudjiono; Budi Darma (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
This study is accomplished to assist the readers of the novel project that is created to understand more about the elements in the novel Deck of Lives. The purpose of this novel is to educate people about the psychological aspects, what cause it and the results, and to support those who have similar psychological disorder. Using the theory of Death Instinct by Freud and Borderline Psychological Disorder, this novel will show the story and the attitudes of the main character. As a conclusion, one cause of the psychological aspects is the neglect and abuse, whether it is emotional, verbal, or physical done by the parents. This will help the readers to understand more of what to do to children to avoid such psychological aspects